2001
DOI: 10.1182/blood.v97.5.1202
|View full text |Cite
|
Sign up to set email alerts
|

Serum nm23-H1 protein as a prognostic factor in aggressive non-Hodgkin lymphoma

Abstract: Advances in chemotherapy have led to a favorable long-term prognosis in approximately 50% of patients with aggressive non-Hodgkin lymphoma (NHL). However, the remaining patients do not enjoy such prolonged survival after standard treatment. New prognostic factors are needed to define this poor-prognosis group and to plan an appropriate treatment strategy. It has been reported that serum nm23-H1 protein may be a new prognostic factor for aggressive NHL. In the present study involving multiple institutions and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 36 publications
2
42
0
Order By: Relevance
“…3 We previously reported that the nm23-H1 protein was strongly expressed on the surface of neoplastic cells of PTCL and extranodal NK/T-cell lymphomas, 4 and we also observed a significant correlation between the serum nm23-H1 level and the degree of its cell surface expression. This suggested that the serum nm23-H1 level reflects the proliferation rate of lymphoma cells, and that, in PTCL and NK-NHL, large amounts of nm23-H1 molecules are secreted from the neoplastic cells.…”
Section: Figuresupporting
confidence: 62%
“…3 We previously reported that the nm23-H1 protein was strongly expressed on the surface of neoplastic cells of PTCL and extranodal NK/T-cell lymphomas, 4 and we also observed a significant correlation between the serum nm23-H1 level and the degree of its cell surface expression. This suggested that the serum nm23-H1 level reflects the proliferation rate of lymphoma cells, and that, in PTCL and NK-NHL, large amounts of nm23-H1 molecules are secreted from the neoplastic cells.…”
Section: Figuresupporting
confidence: 62%
“…Furthermore, high expression of Nm23-H1 has been correlated with poor responses to treatment in high-grade lymphomas other than BL. 12 These observations may therefore have implications for the clinical exploitation of SSRIs in the broader context of B-cell lymphoma. Although a constitutively high bcl-2 expression could potentially compromise such hope, the possibility of combining the delivery of SSRIs with, for example, targeted antisense strategies, could keep this wider possibility open.…”
Section: Discussionmentioning
confidence: 99%
“…10 A recent report has identified that expression of Nm23-H1 may also be linked to c-myc expression, and the high expression of the gene has been correlated with poor responses to treatment in high-grade lymphoma in general. [11][12] Deregulated c-myc expression likely contributes to what appears an apparent dichotomy in the pathobiology of BL: namely aggressive, uncontrolled proliferation coupled with high-rate apoptosis. The latter attribute gives rise to the classical "starry sky" histology that characterizes BL, reflecting the presence of large tingible body macrophages that have been mobilized to the tumor in order to clear the large burden of apoptotic cells generated at these sites.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 28 target proteins of AML1-ETO (12 from 6 h and 16 from 12 h Zn-induced condition) are identified. Two-dimensional gel electrophoresis and mass spectrometry were performed from three independent experiments, and only proteins identified in each of those three experiments were considered to be target proteins of AML1-ETO malignant lymphomas, and neuroblastma [43,44,[46][47][48][49][50][51]. In another study, the cell surface expression of NM23-H1 and H2 was decreased during in vitro erythroid and granulocytic differentiation [43,46].…”
Section: Resultsmentioning
confidence: 99%